2018
DOI: 10.1007/s00702-018-1860-x
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of rotigotine transdermal patch and other currently prescribed therapies in patients with Parkinson’s disease

Abstract: Real-world data from large cohorts of patients with Parkinson's disease on the long-term effectiveness of different dopamine-substituting drug therapies are rare. The objective of this study was to obtain information on real-world management of PD with dopamine-substituting drugs. SP0854 (NCT00599339) was a prospective, multicenter, non-interventional, multiple-cohort, post-authorization safety study of rotigotine versus other dopaminergic therapies. The study was also part of a European Medicines Agency risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…A novel placebo-controlled trial using NMS as a primary outcome measure also showed a significant improvement in motor function, as measured by UPDRS III, and in QoL [36]. A post hoc analysis of six placebo-controlled studies (n>2000) in early or advanced PD confirmed the efficacy of rotigotine on motor symptoms and ADL [37], a finding further supported by a recent review [38], two large metaanalyses [39,40], and a prospective, multisite real-world study in more than 2000 patients with PD of varying stages and symptom severity [41]. A few open-label extension studies have also documented motor benefits lasting up to 6 years [42][43][44][45].…”
Section: Motor Symptoms In Parkinson's Diseasementioning
confidence: 66%
“…A novel placebo-controlled trial using NMS as a primary outcome measure also showed a significant improvement in motor function, as measured by UPDRS III, and in QoL [36]. A post hoc analysis of six placebo-controlled studies (n>2000) in early or advanced PD confirmed the efficacy of rotigotine on motor symptoms and ADL [37], a finding further supported by a recent review [38], two large metaanalyses [39,40], and a prospective, multisite real-world study in more than 2000 patients with PD of varying stages and symptom severity [41]. A few open-label extension studies have also documented motor benefits lasting up to 6 years [42][43][44][45].…”
Section: Motor Symptoms In Parkinson's Diseasementioning
confidence: 66%
“…Twenty-nine trials were national studies. In 22 studies, the Romanian participants were part of international, multicenter studies [101][102][103][104][105][106][107]109,110,[115][116][117]119,[123][124][125][126][127]129,132,141,143]. In the last category, 11 studies were published as original articles [101,102,[115][116][117]119,124,125,129,132,141], and 11 were abstracts presented at international conferences [103][104][105][106][107]109,110,123,126,127,143].…”
Section: Studies On Pharmacological and Non-pharmacological Interventions In Parkinson's Diseasementioning
confidence: 99%
“…,124,125,129,132,141], and 11 were abstracts presented at international conferences[103][104][105][106][107]109,110,123,126,127,143].…”
mentioning
confidence: 99%
“…B. Neupro ® ) mind. genauso gut wirksam und verträglich ist wie die oralen Dopaminagonisten [7][8][9]. Deshalb sollte es gleichberechtigt mit diesen eingesetzt und nicht ausschließlich speziellen Situa tionen vorbehalten werden.…”
Section: Therapiebeginn Mit Dopaminagonistenunclassified